2001
DOI: 10.1007/s00232-001-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Bending the MDCK Cell Primary Cilium Increases Intracellular Calcium

Abstract: We tested the hypothesis that the primary cilium of renal epithelia is mechanically sensitive and serves as a flow sensor in MDCK cells using differential interference contrast and fluorescence microscopy. Bending the cilium, either by suction with a micropipette or by increasing the flow rate of perfusate, causes intracellular calcium to substantially increase as indicated by the fluorescent indicator, Fluo-4. This calcium signal is initiated by Ca2+-influx through mechanically sensitive channels that probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
668
6
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 747 publications
(695 citation statements)
references
References 26 publications
18
668
6
3
Order By: Relevance
“…However, PKD1 and PKD2-mediated Ca 2+ signaling was independent of PLC activation and inhibited by ryonodine and caffeine [62]. These data were in sharp contrast to the data obtained earlier on cilium-bending and fluid flow-induced Ca 2+ signaling in MDCK cells [55], suggesting that PKD1 and PKD2 modulate Ca 2+ signaling through a completely different signaling mechanism from cilium bending. The reasons for these discrepancies are unknown.…”
Section: Function At the Primary Ciliumcontrasting
confidence: 88%
See 1 more Smart Citation
“…However, PKD1 and PKD2-mediated Ca 2+ signaling was independent of PLC activation and inhibited by ryonodine and caffeine [62]. These data were in sharp contrast to the data obtained earlier on cilium-bending and fluid flow-induced Ca 2+ signaling in MDCK cells [55], suggesting that PKD1 and PKD2 modulate Ca 2+ signaling through a completely different signaling mechanism from cilium bending. The reasons for these discrepancies are unknown.…”
Section: Function At the Primary Ciliumcontrasting
confidence: 88%
“…In support of this hypothesis, it has been shown that mechanical bending of the primary cilium or fluid flow in MDCK cells resulted in increases in intracellular Ca 2+ concentration which was dependent on extracellular Ca 2+ , PLC activation and inositol 1,4,5 trisphosphate (IP 3 )-induced release of intracellular Ca 2+ stores [55][56][57]. It is noteworthy that bending-induced Ca 2+ signaling was not affected by inhibition of ryonodine receptors [55]. Several groups have shown the expression of PKD1 and PKD2 in the primary cilium [24,26,58,59].…”
Section: Function At the Primary Ciliummentioning
confidence: 92%
“…Luminal flow has also been shown to induce a rapid increase in intracellular calcium in renal epithelial cells (41,54). In endothelial cells, eNOS activation by flow is independent of calcium and calcium/calmodulin stimulation (11,12,50), arguing against a role for intracellular calcium in eNOS trafficking and activation in the THAL.…”
Section: Discussionmentioning
confidence: 99%
“…In mice lacking P2X 4 receptors, flowinduced increases of [Ca 2+ ] i in the endothelial cells were absent, as was the endothelium-dependent vascular dilatation. Flow-induced increases in [Ca 2+ ] i can also be elicited in renal epithelia [130][131][132]. This phenomenon has received much attention as it was hypothesised that an absence of flow sensing in renal epithelia causes polycystic kidney disease [133].…”
Section: Mechanically Released Nucleotidesmentioning
confidence: 99%